(untitled) (Nigerian Journal of Technology, 2023)
A comparative analysis of the abrasive wear of aluminium alloy and mild steel on the pin-on-disc wear test machine has been successfully carried out. An investigation on the effects of wear, stress and strain on the aluminium alloy and the mild steel was conducted. The wear test carried out determined the difference between rate of wear of the aluminium alloy and the mild steel. The input parameters applied in determining the wear rate were time of wear, sliding distance, track diameter of the disc and mass difference before and after the experiment. The finite element analysis developed the stress and elastic strain distribution obtained on the application of 2 kg load (20 N) on the aluminium alloy and mild steel specimen. The equivalent (Von Mises) stress distribution in mild steel had a maximum stress value of 0.023625 Mpa and minimum stress of 1.444×10-5 Mpa while that of the aluminium alloy yielded a maximum and minimum stress of 0.0365 Mpa and 8.5×10-5 Mpa respectively. It was evident that the aluminium alloy recorded a higher magnitude of stress than the mild steel. This showed that the aluminium alloy being relatively light was more stressed than the mild steel. It was discovered that the rate of wear was higher in the aluminium alloy than in the mild steel.